2010
DOI: 10.1051/orthodfr/2010011
|View full text |Cite
|
Sign up to set email alerts
|

Volumes faciaux et typologie verticale : étude comparative tridimensionnelle

Abstract: Introduction : Le but de cette étude est de comparer les volumes des cavités faciales entre les typologies hyperdivergente et hypodivergente dans une population adulte jeune. Méthodes : Les échantillons étaient formés de 30 sujets chacun, âgés de 18 à 30 ans, sélectionnés selon leur typologie verticale (GoGn-SN ≤ 28° et ≥ 36°). À partir d’acquisitions scanners 3D et à l’aide du logiciel AMIRA®, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 4 However, Oksayan et al 5 and Yassaei et al 6 have shown that maxillary sinus dimensions are reduced in hyper-divergent individuals and vice versa. Goymen et al 7 and Bassil-Nassif et al 8 found no difference in the sinus dimensions among individuals with various mandibular growth patterns. The literature available regarding the relationship of the size of the maxillary sinus and sagittal malocclusion is conflicting.…”
Section: Introductionmentioning
confidence: 94%
“… 4 However, Oksayan et al 5 and Yassaei et al 6 have shown that maxillary sinus dimensions are reduced in hyper-divergent individuals and vice versa. Goymen et al 7 and Bassil-Nassif et al 8 found no difference in the sinus dimensions among individuals with various mandibular growth patterns. The literature available regarding the relationship of the size of the maxillary sinus and sagittal malocclusion is conflicting.…”
Section: Introductionmentioning
confidence: 94%
“…e results of this study demonstrated no significant difference for the volumetric variables A, B, and C between BT and NC groups. A logical explanation could be based on the conclusions from Bassil-Nassif et al [9] advocating the existence of a compensatory mechanism among different facial dimension. ereby, a deficiency of the transverse dimension could be equilibrated by an excess in the vertical and/or the sagittal dimension which leads to maintaining constant the total nasomaxillary volume studied.…”
Section: Comparison Of Before Treatment Group (Bt) and Nc Groupmentioning
confidence: 99%
“…Due to the fact that, the BT group presented linear vertical values higher than those of the NC group, we can join the same rationale of the possibility of compensation of the transverse dimension by an excess of the vertical dimension, which explains further the volumetric concordance between both groups. [9] Cortella et al [2] questioned the theory that transverse dimension growth is the first to be terminated by the fact that maxillary and mandibular width increase varies as sagittal and vertical growth according to gender and chronological age. e greater mandibular than the maxillary transverse growth suggests the existence of a dentoalveolar compensatory mechanism, which permits the preservation of a normal transverse posterior occlusion.…”
Section: Linear and Angular Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical facial type and orthodontic treatment are interrelated, and the alveolar bone, muscle, and malocclusion differ considerably according to the vertical facial type, which can influence therapeutic planning. 1 Vertical facial type is an indicator of craniofacial growth 2 and thus influences the selected treatment and force applied during orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%